THE PROBLEM OF OPTIMAL CONTROL IN THE RUN MODEL - N. I. Ovsyannikova; A. A. Popova (Научный вестник МГТУ ГА)
The article is devoted to the search of optimal control in a model of a middle-distance running in order to minimize the time spent. Control is the force exerted by a sportsman per unit mass - or rather, the acceleration. The initial conditions and constraints on the control are prescribed. In the article optimal control problem is reduced to a fixed-time one by introducing the coefficient of compression of time, which is the second controlling factor.